Do siblings influence one another? Unpacking processes that occur during sibling conflict. Issue 1 (16th August 2022) - Borairi, Sahar; Plamondon, Andre; Rodrigues, Michelle; Sokolovic, Nina; Perlman, Michal; Jenkins, Jennifer
Abstract: This study examined the extent to which 205 sibling dyads influenced each other during conflict. Data were collected between 2013 to 2015. The sample included 5.9% Black, 15.1% South Asian, 15.1% East Asian, and 63.8% White children. Older siblings were between 7–13 years old (Female = 109) and younger siblings were 5–9 years old (Female = 99). Siblings' conflict resolution was analyzed using dynamic structural equation modeling. Modeling fluctuations in moment‐to‐moment data (20‐s intervals) allowed for a close approximation of causal influence. Older and younger siblings were found to influence one another. Younger sisters were more constructive than younger brothers, especially in sister–sister dyads. Sibling age gap predicted inertia in older siblings. Socialization processes within sibling relationships are discussed.